Analysis of disk cam motion for follower shape in horizontal position - Mohd Sobri, Husain (2008)
This thesis is a analyzing of disk cam motion follower shape in horizontal position using roller follower. The objective of this thesis is to analyze disk cam profile using roller follower that neglected the friction as the interruption. This thesis also analyzes the disk cam motion in horizontal follower position. The performance of the disk cam mechanism system is based upon the shape of the cam, type of the follower that will be used, and what the application that the cam is used it, wherever high speed application or low speed application. The method that will be used in analyzing the disk cam mechanism in this thesis is two, using the theoretical manner that is graphical method and the experimental method using the Dewesoft software. The comparison between these two methods will be discussed and the characteristics of this shape of the cam will be analyzed. From this thesis, show that this type of cam only suitable for low speed application because it will endure the high vibration while operating in high sped application. Vibration is some sort of cause of failure to the mechanism that can give disadvantage to the industries nowadays. It also causes the system to go unbalance while operating and draw the system to fail if no action that will take.